Optimasi Microwave Assisted Extraction Daun Dewandaru (Eugenia uniflora L.) Sebagai Aplikasi Tabir Surya pada Sediaan Body Lotion - Khoirul Anwar; Gharsina Ghaisani Yumni; Ayu Shabrina; Aulia Septiani Putri; Melani Putri Britama; Sugito Chandra (Universitas Tidar, 2026)
Excessive exposure to ultraviolet (UV) radiation can cause various skin disorders, highlighting the need foreffective and safe sunscreen products. This study aimed to optimize the extraction of dewandaru leaves(Eugenia uniflora L.) using Microwave-Assisted Extraction (MAE) and to evaluate their potential as a naturalsunscreen active ingredient in body lotion formulations. Optimization was carried out using Response SurfaceMethodology (RSM) by varying extraction temperature and time. The results showed that the optimumextraction condition was achieved at 80 °C for 30 minutes, producing an extract yield of 31.88% and a SunProtection Factor (SPF) value of 39.90, categorized as ultra protection. Phytochemical screening and FTIRanalysis confirmed the presence of phenolic and flavonoid compounds responsible for photoprotective activity.Body lotion formulations containing 5%, 10%, and 15% extract met the required physical quality parameters,including homogeneity, pH, viscosity, spreadability, adhesiveness, and oil-in-water (O/W) emulsion type. Thesefindings indicate that dewandaru leaf ethanol extract has strong potential as an effective and safe naturalsunscreen active ingredient. Keywords: Eugenia uniflora; Microwave-Assisted Extraction; SPF; natural sunscreen; body lotion